MENINGKATKAN KETUNTASAN SISWA MELALUI MODEL PEMBELAJARAN INKUIRI - Masiah, Masiah (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This study aims to improve student completeness through inquiry learning models. This research is a Classroom Action Research (CAR), consisting of stages which include: 1) planning; 2) implementation; 3) actions; 4) observation; and 5) reflection. Data collection techniques carried out by observation and tests. Data collection techniques using quantitative descriptive. The results of the study in the first cycle showed an increase in completeness of the initial conditions of students that is 72%, an increase of 20% from the previous, or there were 18 students who completed and the remaining 7 students were incomplete. Increased completeness in the first cycle has not yet reached the classical completeness that is â‰¥85%, so it needs to be continued to the second cycle. Actions in the second cycle are carried out based on the results of reflection in the previous cycle. After an improvement in cycle II, there was an increase in student completeness as many as 22 students who entered the complete category, or about 88% and the remaining 12% were incomplete. Achievement of completeness in the first cycle was 72%, and in the second cycle was 88%, resulting in an increase of 12%. Based on the achievements in the second cycle, it can be concluded that inquiry learning can improve student completeness.